Health Beliefs in Association with Behaviors in Compliance with COVID-19 Public Health Guidelines: A Cross-sectional Study. Issue 1 (2nd January 2022) - Can, Fatma; Ergül-Topçu, Aysun; Topçu, Gökhan
ABSTRACT: This study investigated the preventive health behaviors against the COVID-19 outbreak in Turkey according to the health belief model. The relationships between perceived susceptibility, severity, benefits, barriers, and preventive health behaviors were examined. 1401 participants consisting of 992 (70.8%) females and 409 (29.3%) males participated in an online survey. Independent groups t-test, hierarchical regression analysis and Process Macro were used for analyses. The findings showed that women perceived higher levels of severity of the disease and the benefits of preventive health behaviors than men. Men perceived more barriers to preventive health behaviors. The levels of anxiety and preventive health behaviors of women were higher than men. In regression analysis, male gender and perceived barriers were found as risk factors for preventive health behaviors. However, female gender, perceived severity, and benefits were protective factors for preventive health behaviors. People with low and moderate anxiety levels were more likely to comply with preventive health behaviors.